Alcoholic ketoacidosis that developed with a hypoglycemic attack after eating a high‐fat meal. Issue 2 (16th December 2013) - Suzuki, Kei; Tamai, Yasuyuki; Urade, Shinji; Ino, Kazuko; Sugawara, Yumiko; Katayama, Naoyuki; Hoshino, Tamotsu
<x xml:space="preserve">Abstract</x> Case Alcoholic ketoacidosis (AKA) usually occurs in patients with a history of prolonged alcohol abuse and recent binge drinking followed by abrupt cessation of alcohol consumption. Outcome A 61‐year‐old man was brought to our emergency department. He had a history of eating barbecued beef with beer the previous night. He had unexplained hypoglycemia with high anion gap metabolic acidosis and fatty liver, and we strongly suspected AKA. After hydration with saline solution, dextrose, and thiamine, given i.v., his metabolic acidosis rapidly improved. A history of alcohol abuse and high serum β‐hydroxybutyrate concentration were subsequently confirmed, and the diagnosis of AKA was finally made. Conclusion Our case suggests that a high‐fat meal can induce AKA without abrupt cessation of alcohol consumption and that AKA should be considered when encountering patients with unexplained high anion gap metabolic acidosis with hypoglycemia and fatty liver, even if the past history of alcohol abuse is unknown.